Respuesta :

[tex](\stackrel{x_1}{2}~,~\stackrel{y_1}{2})\qquad (\stackrel{x_2}{-1}~,~\stackrel{y_2}{20}) ~\hfill \stackrel{slope}{m}\implies \cfrac{\stackrel{rise} {\stackrel{y_2}{20}-\stackrel{y1}{2}}}{\underset{run} {\underset{x_2}{-1}-\underset{x_1}{2}}}\implies 6 \\\\\\ \begin{array}{|c|ll} \cline{1-1} \textit{point-slope form}\\ \cline{1-1} \\ y-y_1=m(x-x_1) \\\\ \cline{1-1} \end{array}\implies y-\stackrel{y_1}{2}=\stackrel{m}{6}(x-\stackrel{x_1}{2})[/tex]

Answer:  y-2 = -6 (x-2)

Step-by-step explanation: Point slope form is this equation:

y-y1 = m (x-x1)

y1 is 2 because (2,2) ; The left 2 is x1 and the right 2 is y1.

(-1,20); The -1 is x2 and the 20 is y2.

If you use the equation above it helps a lot. I hope this helps you! :)

ACCESS MORE